TorakochirurgiaFollow-up study of the treatment of patients for tracheal tumours - Czajkowski, Wojciech; Olechnowicz, Henryk; Gawrychowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Aim: The aim of the study was to evaluate the effectiveness of tracheal tumour treatment based on the analysis of survival, therapeutic management and effect of palliative procedure on improvement in general condition of the patients and their spirometric parameters. Material and methods: Between 1989 and 2004, 124 patients were treated for tracheal tumours and/or tracheal bifurcation. Thirty-four patients underwent radical operative treatment, and 90 were referred for palliative type. After eliminating 8 (6.5%) who died within 30 days of hospital stay, the study included 116 patients discharged from our Department, 77 (66.7%) men and 39 (33.6%) women aged 17-78, mean 56.4 years. Results: After operative treatment for tracheal tumours, 5-year survival was observed in 49.7%, but after palliative treatment only 6.8% (P<0.001). Medians were 27.5 and 3.5 months respectively. Among 26 patients who underwent radical resection, 57% survived 5 years. Median was 79 months. After segmentary tracheal resection 76% of the patients survived 5 years, but when such resection was accompanied by resection of tracheal bifurcation, only 22.5% survived 5 years (P=0.003). Medians were 100 months and 11.5 months respectively. A statistically significant improvement in general condition of patients was observed after operative treatment as compared to their pre-operative condition (P=0.018), as well as in the palliative group before and after treatment (p=0.039). No statistically significant differences were observed in spirometric examinations before and after operation either in lung vital capacity (VC) (P=0.075) or forced first-second expiratory volume (FEV1) (p=0.348). On the other hand, in the palliative group these differences were statistically significant both for VC (P<0.001) and FEV1 (P<0.001). Conclusions: 1. Radical operative resection followed by restoration of tracheo-bronchial tree continuity is an effective method for treating tracheal tumours or bifurcation, and provides the best late results. 2. Mechanical restoration of patency in the bronchial tree followed by stent insertion and radiotherapy and/or chemotherapy is the management of choice in patients with inoperative tracheal tumours. 3. Palliative treatment in patients with inoperative tracheal tumours or tracheal bifurcation enables a substantial improvement to be achieved in patients’ quality of life.